98.3k views
5 votes
Given x=t³-3t and y=3t², find the value of dy/dx at t=√2​

User Kanti
by
5.4k points

1 Answer

4 votes

Answer:

The value of
\frac{\mathrm{d} y}{\mathrm{d} x} at t = √2 is
(1)/(2 * √(2)) .

Explanation:

Given as :

x = t³ - 3 t

y = 3 t²

We have to calculate
\frac{\mathrm{d} y}{\mathrm{d} x} at t = √2

Now,


\frac{\mathrm{d} x}{\mathrm{d} t} =
\frac{\mathrm{d} (t³ - 3 t)}{\mathrm{d} t}

Or,
\frac{\mathrm{d} x}{\mathrm{d} t} =
\frac{\mathrm{d}  t³}{\mathrm{d} t} - 3
\frac{\mathrm{d}  t}{\mathrm{d} t}

Or,
\frac{\mathrm{d} x}{\mathrm{d} t} = 3 t² - 3
......A

Again


\frac{\mathrm{d} y}{\mathrm{d} t} =
\frac{\mathrm{d} (3 t²)}{\mathrm{d} t}

Or,
\frac{\mathrm{d} y}{\mathrm{d} t} = 3 × 2 t

Or,
\frac{\mathrm{d} y}{\mathrm{d} t} = 6 t
......B

So,


\frac{\mathrm{d} y}{\mathrm{d} x} =
((\partial y)/(\partial t))/((\partial x)/(\partial t))

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} =
(3 t^(2) - 3 )/(6 t)

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} =
(3(t^(2)-1))/(6 t)

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} =
((t^(2)-1))/(2 t)

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} at t = √2

i.e
\frac{\mathrm{d} y}{\mathrm{d} x} =
((√(2)^(2)-1))/(2 * √(2))

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} =
((2-1))/(2 * √(2))

Or,
\frac{\mathrm{d} y}{\mathrm{d} x} =
(1)/(2 * √(2))

Hence, The value of
\frac{\mathrm{d} y}{\mathrm{d} x} at t = √2 is
(1)/(2 * √(2)) . Answer

User Motassem Jalal
by
6.1k points